Exterior view of th Comet Masonic Lodge, Barcaldine, Queensland, 24 May 2019, 1 - Chapman, Andrew, 1954- (2019)
The Comet Masonic Lodge at Barcaldine, Queensland. Corrugated iron building with hand painted chamferboard front, 24 May 2019--Information supplied by photographer.
Title devised by cataloguer based on information supplied by photographer.
Part of the collection: The Barcaldine Masonic Lodge and a old corrugated iron shed, Queensland, 2019.
Keywords: Barcaldine Masonic Lodge (Qld.) -- Photographs; Freemasons -- Queensland -- Barcaldine -- Photographs; Freemasonry -- Queensland -- Barcaldine -- Photographs; Temples -- Queensland -- Barcaldine -- Photographs; Vernacular architecture -- Queensland -- Barcaldine -- Photographs; Barcaldine (Qld.) -- Buildings, structures, etc. -- Photographs